2014
DOI: 10.5455/ijmsph.2014.040420145
|View full text |Cite
|
Sign up to set email alerts
|

Screening and manifestations of seropositive dengue fever patients in Perambalur: A Hospital based study

Abstract: Background: Dengue infection is the most important one in terms of morbidity and mortality. If the illness is not identified early in the course and not treated promptly when indicated, case fatality rate of DHF can go over 20% and that of DSS can be as high as 44%. Aims & Objective:To study the manifestations of seropositive dengue fever patients at tertiary care hospital Perambalur. Also to assess indicators associated with poor prognosis (DHF and DSS) for early recognition of complications. Materials and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
(7 reference statements)
4
2
0
Order By: Relevance
“…We can see from table 2, the value of mean MPV increases as the platelets count increases. This is in accordance with the study conducted by Bashir, et al, 2015, Anuradha, et al, 2014, Navya, et al, 2016and Mukker, et al, 2018 They also observed low value of mean platelet volume (MPV) with low platelet count. Navya, et al,2016 in their study group of 100 patients, saw a mean MPV of <9 fl in 72% of patients.…”
Section: Discussionsupporting
confidence: 91%
“…We can see from table 2, the value of mean MPV increases as the platelets count increases. This is in accordance with the study conducted by Bashir, et al, 2015, Anuradha, et al, 2014, Navya, et al, 2016and Mukker, et al, 2018 They also observed low value of mean platelet volume (MPV) with low platelet count. Navya, et al,2016 in their study group of 100 patients, saw a mean MPV of <9 fl in 72% of patients.…”
Section: Discussionsupporting
confidence: 91%
“…Study by Anuradha M et al showed 89% cases with thrombocytopenia which was slightly more than the present study (77.33%). [11,12,13] In the study conducted by Manoharan A et al, MPV was found to be high in patients with bleeding manifestations which similar to the present study. Afsar N et al found a statistically significant p value in their study of MPV which was concurrent with our study.…”
Section: Discussionsupporting
confidence: 90%
“…In present study, thrombocytopenia (platelet count <1 lakh/mm 3 Chatterjee et al, thrombocytopenia was observed in 69.15%, 84.66%, 62%, 60% and 55.5% respectively. 9,12,13 The levels of AST and ALT (>40 IU/L) were elevated in 39 (29.54.%) case and 32 (24.44%), analogous findings of AST and ALT were observed by Khan et al, 40.66% and 28% respectively. 9 However, in a study done by Deshwal et al, AST was raised in 88.5% and ALT was raised in 88% cases.…”
Section: Discussionsupporting
confidence: 64%